The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10856-012-4612-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel bioactive vitroceramic presents similar biological responses as autogenous bone grafts

Abstract: Bioactive glasses represent an interesting class of bone substitute's biomaterials. The present study investigated the repair of bone defects filled with a novel bioactive vitroceramic (Biosilicate(®)), alone or in association with particulate autogenous bone grafts in calvaria defects of rabbits. After 7, 14, and 30 days the specimens were retrieved for histological, histomorphometric and immunohistochemistry analysis. Satisfactory bone formation was observed in all groups, and direct bone-biomaterial surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
2
23
0
2
Order By: Relevance
“…According to previous studies, the quantity of positive cells per field was described by a scoring scale from 1 to 4 (1 = absent, 2 = weak, 3 = moderate, and 4 = intense). 19,20 The analysis was performed by two observers (C.T. and K.N.Z.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…According to previous studies, the quantity of positive cells per field was described by a scoring scale from 1 to 4 (1 = absent, 2 = weak, 3 = moderate, and 4 = intense). 19,20 The analysis was performed by two observers (C.T. and K.N.Z.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Matsumoto et al [25] in a study using rabbit calvaria observed that Biosilicate associated with autogenous bone showed histometric and immunohistochemical results similar to the defects which were filled with nothing but autogenous bone. The microscopic analyses showed very similar neoformed tissue in both groups, suggesting that the degradation level of the biomaterial tends to be compatible to the bone formation.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, internal positive controls were performed with each staining bath. RUNX2 and RANK-L immunoexpressions were evaluated both qualitatively (presence of the immunomarkers) and quantitatively in five predetermined fields using light microscopy (Leica Microsystems AG, Wetzlar, Germany) according to a previously described scoring scale from 1 to 4 (1=absent, 2=weak, 3=moderate, and 4=intense) for immunohistochemical analysis [20,21]. The analysis was performed by two observers in a blinded way.…”
Section: Immunohistochemistrymentioning
confidence: 99%